1982
DOI: 10.1021/jm00344a007
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures and pharmacological activity of calcium channel antagonists: 2,6-dimethyl-3,5-dicarbomethoxy-4-(unsubstituted, 3-methyl-, 4-methyl-, 3-nitro-, 4-nitro-, and 2,4-dinitrophenyl)-1,4-dihydropyridine

Abstract: The molecular structures of 2,6-dimethyl-3,5-dicarbomethoxy-4-phenyl-1,4-dihydropyridine and the 3-methyl-, 4-methyl-, 3-nitro-, 4-nitro-, and 2,4-dinitrophenyl derivatives were determined by X-ray diffraction methods. The dihydropyridine ring in each of the compounds exists in a boat-type conformation. However, the degree of ring puckering varies among the compounds. The observed ring distortions were found to be influenced to a great extent by the position of the substituent in the 4-phenyl ring and the conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
0
1

Year Published

1984
1984
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(62 citation statements)
references
References 2 publications
7
54
0
1
Order By: Relevance
“…A large ring distortion is seen at C4 and N1. This feature is observed in other dihydropyridine derivatives (Fossheim et al, 1982;Tamazawa et al, 1986). Lorentz and polarization corrections were applied to the data.…”
Section: H (I)supporting
confidence: 59%
“…A large ring distortion is seen at C4 and N1. This feature is observed in other dihydropyridine derivatives (Fossheim et al, 1982;Tamazawa et al, 1986). Lorentz and polarization corrections were applied to the data.…”
Section: H (I)supporting
confidence: 59%
“…Two (1)-C(2) 1.370 (3) C17HITN304 AND Clgn2oN206 constraining the orientation of the phenyl ring to lie close to the N(1)-C(4) vertical symmetry plane of the 1,4-DHP ring (Loev et al, 1974;Rodenkirchen, Bayer, Steiner, Bossert, Meyer &Moller, 1979). Diffraction studies (Triggle, Shefter & Triggle, 1980;Fossheim, Swarteng, Mostad, Romming, Shefter & Triggle, 1982) confirmed this intramolecular constraint and furthermore revealed that antagonist potency correlated more strongly with the degree of DHP ring flatness than with the degree of phenyl ring rotational coplanarity with the N(1)-C(4) DHP vertical symmetry plane. In such structures the DHP ring has a shallow boat conformation with N(1) and C(4) defining the stern and bow positions, the aryl group is situated above the bow of the boat in an axial or flagpole orientation with the ortho or meta substituent almost invariably positioned on the forward or bowsprit side of the phenyl ring.…”
Section: Dicarboxyalkyl-4-(ortho/meta-substituted-phenyl)-14-mentioning
confidence: 76%
“…(1) Å and 0.151 (2) Å, respectively, from the plane defined by C8, C9, C10, and C11, and form the apexes of a boat-type conformation (Fossheim et al, 1982).…”
Section: Methodsmentioning
confidence: 99%
“…For ring conformations and ring puckering analysis, see: Boeyens (1978); Cremer & Pople (1975). For related 1,4-dihydropyridine structures, see : Fossheim et al (1982); Teng et al (2008); Bai et al (2009). For the stability of the temperature controller used in the data collection, see : Cosier & Glazer (1986).…”
Section: Related Literaturementioning
confidence: 99%